Identification of predominant signaling pathway in osteogenic gene regulation of dental pulp stem cells by collagen type 1 induction - Hadri, Nurulhuda Athirah (2023)
Stem cells-based regenerative therapy offers a promising approach for the treatment of bone fractures and craniofacial bone reconstruction. A harmonious interplay between stem cells, scaffolds, and growth factors is the key to successful osteogenic differentiation and subsequent bone formation. The main component of the bone extracellular matrix, Collagen type 1 (Col 1) has been widely proposed as a suitable material for bone tissue engineering, with excellent evidence on biocompatibility and osteoconductivity. However, the key signaling pathway associated with Col type 1-induced osteoblast proliferation and differentiation remains underexplored. The present study investigated the osteoinductive capacity of Col 1 in inducing the osteogenic differentiation of dental pulp stem cells (DPSC). A total of 10,000 cells/cm2 cells were plated in various combination of Col I + Matrigel™, without the presence of other external inducing factors. Alizarin red staining and PCR analysis were performed to ascertain bone nodule deposition and osteogenic genes (OPN, OCN, Osx) expression. Further analysis was performed with inhibitors to assess the predominant signaling pathway involved in Col 1 induction of DPSC into forming committed bone cells. DPSC induced with selected scaffold- Col 1 at 2mg/ml were treated with pathway inhibitors LY294002, LY3200882, and PD98059 targeting AKT, Smad, and ERK signaling respectively. The pathway inhibition assay was performed on the cells at day 7, 14 and 21, followed by alizarin red staining and qRT-PCR analysis. Col 1 was described to induce spontaneous osteoblast differentiation of DPSC in the absence of any osteogenic stimulant. Gene expression analysis revealed the involvement of all investigated pathways especially the ERK signaling in modulating DPSC osteogenesis by Col 1 induction. The data provided by this study, on the fundamental knowledge of stem cells biology and scaffold component may then be used to design an efficient stem cell-based treatment in accelerating the process of bone repair and regeneration.